Unsteady Flow of Reactive Viscous, Heat Generating/Absorbing Fluid with Soret and Variable Thermal Conductivity - I. J. Uwanta; M. M. Hamza (International Journal of Chemical Engineering)
This study investigates the unsteady natural convection and mass transfer flow of viscous reactive, heat generating/absorbing fluid in a vertical channel formed by two infinite parallel porous plates having temperature dependent thermal conductivity. The motion of the fluid is induced due to natural convection caused by the reactive property as well as the heat generating/absorbing nature of the fluid. The solutions for unsteady state temperature, concentration, and velocity fields are obtained using semi-implicit finite difference schemes. Perturbation techniques are used to get steady state expressions of velocity, concentration, temperature, skin friction, Nusselt number, and Sherwood number. The effects of various flow parameters such as suction/injection (γ), heat source/sinks (S), Soret number (Sr), variable thermal conductivity δ, Frank-Kamenetskii parameter λ, Prandtl number (Pr), and nondimensional time t on the dynamics are analyzed. The skin friction, heat transfer coefficients, and Sherwood number are graphically presented for a range of values of the said parameters.